Co-occurrence of Chronic Musculoskeletal Pain and Cardiovascular Diseases: A Systematic Review with Meta-Analysis - Oliveira, Crystian B [UNESP]; Maher, Chris G; Franco, Marcia R; Kamper, Steven J; Williams, Christopher M; Silva, Fernanda G [UNESP]; Pinto, Rafael Z (Oxford University Press (OUP), 2020)
Objective: To determine the magnitude of the association between cardiovascular disease and chronic musculoskeletal pain. Design: Systematic review with meta-Analysis. Methods: A comprehensive search was performed in five electronic databases. Population-based studies reporting the prevalence of cardiovascular diseases in adults stratified by chronic musculoskeletal pain status were considered eligible. Two independent reviewers performed the screening of the records following the inclusion criteria, extracted data, and evaluated the risk of bias of the included studies using an assessment tool of risk of bias for observational studies. In addition, we assessed the overall quality of evidence using an adaptation of the GRADE approach for prognosis. Results: Twenty studies were included in this review. There was high-quality evidence that people with chronic musculoskeletal pain are 1.91 times more likely to report having a cardiovascular disease compared with those without chronic musculoskeletal pain (risk ratio = 1.91, 95% confidence interval = 1.64-2.21). Conclusions: Our findings demonstrated associations between chronic musculoskeletal pain and any cardiovascular diseases. Future studies are still warranted to better understand the association between chronic musculoskeletal pain and the specific types of cardiovascular diseases.
Keywords: Cardiovascular Diseases; Chronic Musculoskeletal Pain; Prevalence